C4-arylation and domino C4-arylation/3, 2-carbonyl migration of indoles by tuning Pd catalytic modes: Pd(i)–Pd(ii) catalysis vs. Pd(ii) catalysis. Issue 9 (19th January 2021) - Cheng, Yaohang; Yu, Shijie; He, Yuhang; An, Guanghui; Li, Guangming; Yang, Zhenyu
Abstract : C4-arylation via Pd(i )–Pd(ii ) catalysis and domino C4-arylation/3, 2-carbonyl migration of indoles via Pd(ii ) catalysis tuning by acids have been developed. Abstract : Efficient C4-arylation and domino C4-arylation/3, 2-carbonyl migration of indoles have been developed. The former route enables C4-arylation in a highly efficient and mild manner and the latter route provides an alternative straightforward protocol for synthesis of C2/C4 disubstituted indoles. The mechanism studies imply that the different reaction pathways were tuned by the distinct acid additives, which led to either the Pd(i )–Pd(ii ) pathway or Pd(ii ) catalysis.